ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH INSTAGRAM TERHADAP BRAND IMAGE DAN PURCHASE INTENTION STUDI PADA LABACO BARBERSHOP DAN CAFE KENDARI - Lestari Daswan; Juharsah Juharsah; Nasrul Nasrul (Pascasarjana Universitas Halu Oleo, 2019)
This study aims to determine the effect of electronic word of mouth (eWOM) instagram toward brand image, the effect of e-WOM instagram toward purchase intention, the effect of brand image toward purchase intention, and the effect of brand image as intervening variable among eWOM toward purchase intention. The research uses simple random sampling technique. There are 100 respondents who have instagram account taken as samples as they are friends of Labaco Barbershop and Café on instagram. The technique of data analysis uses SEM (Structural Equation Modeling) analysis. The result of the study showed that eWOM instagram has an effect on brand image, eWOM instagram has an effect on purchase intention, brand image has an effect on purchase intention, and brand image has a role as the intervening variable among eWOM instagram toward purchase intention at Labaco Barbershop and Café in Kendari Municipality.